Polymethoxylated flavones, flavanone glycosides, carotenoids, and antioxidants in different cultivation types of tangerines (citrus reticulata blanco cv. sainampueng) from Northern Thailand - Stuetz W. (2017)
Polymethoxylated flavones (PMFs) and flavanone glycosides (FGs) were analyzed in hand-pressed juice and the peeled fruit of Sainampueng tangerines (Citrus reticulata Blanco cv. Sainampueng) grown in northern Thailand. The tangerines were collected from a citrus cluster of small orchard farmers and were cultivated as either agrochemical-based (AB), agrochemical-safe (AS), or organic grown fruits. Juice samples were also measured on contents of carotenoids, ascorbic acid, and tocopherols. The peel-deriving PMFs tangeretin, nobiletin, and sinensetin were found with high concentrations in juice as a result of simple squeezing, whereas amounts of those PMFs were negligibly low in peeled tangerine fruit. In contrast, the mean concentrations of the FGs narirutin, hesperidin, and didymin were several fold higher in peeled fruit than in tangerine juice and significantly higher in organic than AS and AB tangerines. Narirutin and hesperidin in juice from organic produces as well as narirutin in juice from AS produces were significantly higher than respective mean concentrations in juice from AB produces. β-Cryptroxanthin was the predominant carotenoid beside zeaxanthin, lutein, lycopene, and β-carotene in tangerine juice. Ascorbic acid concentrations were not predicted by the type of cultivation, whereas α-tocopherol was significantly higher in juice from organic than AS produces. In summary, hand-pressed juice of C. reticulata Blanco cv. Sainampueng serves as a rich source of PMFs, FGs, carotenoids, and antioxidants: 4-5 tangerine fruits (∼80 g of each fruit) giving one glass of 200 mL hand-pressed juice would provide more than 5 mg of nobiletin and tangeretin and 36 mg of hesperidin, narirutin, and didymin, as well as 30 mg of ascorbic acid, > 1 mg of provitamin A active β-cryptoxanthin, and 200 μg of α-tocopherol. © 2010 American Chemical Society.